Analisis Tasybih, Isti‘arah, dan Majaz dalam Al-Qur’an serta Metode Pembelajarannya - Nurhidayah, Nurhidayah; Sidik, Anwar (Indo Publishing, 2026)
This study examines the use of tasybih, isti‘arah, and majaz in the Qur’an as important elements of Arabic rhetoric (balaghah) that contribute to the beauty, clarity, and depth of Qur’anic language. The Qur’an, as the miracle of Prophet Muhammad SAW, contains numerous verses describing creation, including natural phenomena such as plants, humans, and the universe, which strengthen faith and awareness of Allah’s power. Using a qualitative library research approach, this study analyzes verses of the Qur’an containing rhetorical devices alongside relevant balaghah literature. The findings show that tasybih functions as an explicit comparison to clarify abstract meanings, isti‘arah conveys metaphorical meanings through borrowed expressions to strengthen messages, and majaz expands meaning beyond literal interpretation while maintaining contextual relevance. These rhetorical styles not only enhance linguistic aesthetics but also serve moral, spiritual, and communicative purposes. Furthermore, understanding these forms is essential in Qur’anic interpretation, as many verses cannot be fully understood through literal meaning alone. Therefore, mastery of balaghah is crucial for appreciating the miraculous language of the Qur’an and for gaining a deeper, more contextual understanding of its teachings.